2021
DOI: 10.1039/d1cy00446h
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective direct, base-free hydrogenation of ketones by a manganese amido complex of a homochiral, unsymmetrical P–N–P′ ligand

Abstract: The use of manganese in homogeneous hydrogenation catalysis has been a recent focus in the pursuit of more environmentally benign base metal catalysts. It has great promise with its unique...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…Among them, Mn I ‐catalyzed asymmetric hydrogenation [10] and transfer hydrogenation [11] are much more attractive, and expected to acquire more eye‐catching achievements. Considering the wide applications of multidentate PNP, [9a–f, 10a–c, 11a,f] PNN, [9g–i, 10d–g, 11b] and NNN [9j–l] pincer ligands in manganese catalysis and based on the continuing efforts of our group in asymmetric hydrogenation, [12] we envisioned that the above designed chiral N 6 ‐macrocyclic ligands could be applied in Mn I ‐catalyzed asymmetric catalysis. To the best of our knowledge, there is no report on Mn I ‐catalyzed enantioselective reactions by utilizing a chiral peraza macrocyclic ligand so far.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Mn I ‐catalyzed asymmetric hydrogenation [10] and transfer hydrogenation [11] are much more attractive, and expected to acquire more eye‐catching achievements. Considering the wide applications of multidentate PNP, [9a–f, 10a–c, 11a,f] PNN, [9g–i, 10d–g, 11b] and NNN [9j–l] pincer ligands in manganese catalysis and based on the continuing efforts of our group in asymmetric hydrogenation, [12] we envisioned that the above designed chiral N 6 ‐macrocyclic ligands could be applied in Mn I ‐catalyzed asymmetric catalysis. To the best of our knowledge, there is no report on Mn I ‐catalyzed enantioselective reactions by utilizing a chiral peraza macrocyclic ligand so far.…”
Section: Introductionmentioning
confidence: 99%
“…This species could also be observed in the 1 H NMR spectrum, which exhibited a hydride triplet signal at −5.67 ppm . Very recently, Morris and co-workers demonstrated that Mn–H species with an unsymmetrical P–N–P′ ligand appear at −4.4 ppm . Thus, an NMR experiment was performed using complex Mn-1 as the precatalyst in the presence of 2 equiv of KO t Bu and 14 equiv of isopropyl alcohol in toluene- d 8 at room temperature for 2 h. The 1 H NMR spectrum exhibited hydride peaks at −4.77 and −4.63 ppm, which are attributed to the formation of a Mn hydride species (Figure ).…”
Section: Resultsmentioning
confidence: 85%
“…7 Very recently, Morris and co-workers demonstrated that Mn−H species with an unsymmetrical P−N−P′ ligand appear at −4.4 ppm. 27 Thus, an NMR experiment was performed using complex Mn-1 as the precatalyst in the presence of 2 equiv of KO t Bu and 14 equiv of isopropyl alcohol in toluene-d 8 at room temperature for 2 h. The 1 H NMR spectrum exhibited hydride peaks at −4.77 and −4.63 ppm, which are attributed to the formation of a Mn hydride species (Figure 4). Possibly, there are two isomers of Mn hydride species with the hydride anti or syn to the t-Bu group.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[91] Further developments from the group also include using the racemic version of 37 to reduce enantioenriched -chiral esters without a loss of stereochemistry. [92] The group of Beller, [93] Zhong, [94] Wen and Zhang, [95] Morris, [96] and Wang, Han and Ding [97] have all also added to the field of asymmetric ketone hydrogenation using an enantiomerically enriched chiral manganese complex. Ar = Ph) [91,98] (For Ding and Han et al catalyst 41: variations of Ar were used for the 2019 and 2020 publications) [97] Nitrile hydrogenation has only been replicated, since Beller's original 2016 publication (with catalyst 27, Scheme 10), using diphosphine bidentate ligands on a Mn(I) center ('type E').…”
Section: Accepted Manuscriptmentioning
confidence: 99%